2011
DOI: 10.3892/mmr.2011.726
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effect and apoptosis induction by quercetin in the human lung cancer cell line A-549

Abstract: Abstract. The aim of the present study was to investigate the anticancer effect of quercetin (QC) in the human lung cancer cell line A-549 and further study the mechanism of apoptosis induction by QC. Low differentiation potential A-549 human lung cancer cells were treated with QC at different doses and for different times, and the growth inhibitory rates were detected by MTT assay. Apoptosis induced by QC in A-549 cells was observed by Annexin V/PI double staining and flow cytometric assay. The relative tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 16 publications
3
45
0
3
Order By: Relevance
“…Zheng et al showed that quercetin revealed its anticancer effect by induction of apoptotic mechanism on A549 lung cancer cell lines in time-and dose-dependent manner in accordance with our results (21). In order to determine networks and pathways regulated by quercitrin treatment in NSCLC and lung fibroblast cells, we performed Illumina Human HT-12v4 beadchip microarrays on A549, NCI-H358, and MRC5 cells.…”
Section: Discussionsupporting
confidence: 86%
“…Zheng et al showed that quercetin revealed its anticancer effect by induction of apoptotic mechanism on A549 lung cancer cell lines in time-and dose-dependent manner in accordance with our results (21). In order to determine networks and pathways regulated by quercitrin treatment in NSCLC and lung fibroblast cells, we performed Illumina Human HT-12v4 beadchip microarrays on A549, NCI-H358, and MRC5 cells.…”
Section: Discussionsupporting
confidence: 86%
“…In Japan, the average quercetin intakes were 16.2 mg/day [3]. The antibacterial [4], antiviral [5], antiallergic [6], anticarcinogenic [7,8] and antioxidant [9,10] properties of quercetin were widely studied and described. Moreover, quercetin can effectively chelate metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have demonstrated that quercitrin exhibits various biological activities, including antioxidant, anti-infl ammatory, and anti-cancer properties [23]. Several studies suggest that the anti-tumor effects of quercitrin are mediated by inhibiting the metastatic potential of prostate cancers cells and melanoma and by restraining tumor angiogenesis [24,25].…”
Section: Discussionmentioning
confidence: 99%